Beginning behavioral research : a conceptual primer - ROSNOW, Ralph L.; Robert Rosenthal (New Jersey : Prentice Hall, 2002)
Suitable for students who are required to plan, analyze, and interpret empirical studies and the data they generate, this book features coverage of statistical power and effect size and an optional discussion of meta-analysis, along with coverage of the research process.
Includes bibliography and index
Keywords: Psychology -- Research -- Methodology -- Textbooks; Social sciences -- Research -- Methodology -- Textbooks; Psychology -- Research -- Methodology